Tree ring blue intensity-based August temperature reconstruction for subtropical central China - Zheng, Yonghong; Wilson, Rob (Forests, 2024)
Funding: This research was funded by the Key Regional Joint Research Program of the National Natural Science Foundation of China, grant no.U23A2021, and the National Natural Science Foundation of China, grant no.41771227. Rob Wilson was further funded by the NSF/NERC project, grant no. NE/W007223/1 – Understanding Trans-Hemispheric Modes of Climate Variability: A Novel Tree-Ring Data Transect spanning the Himalaya to the Southern Ocean. Tree-ring blue intensity (BI) has the potential to provide information on past summer temperatures of a similar quality to that of tree-ring maximum latewood density and at a substantially reduced cost. To explore the applicability of BI in subtropical regions, the inverted BI for the earlywood, latewood, and the delta BI (DBI) parameters, together with tree-ring width of subalpine fir (Abies fargesii Franch.) in the Shennongjia area of China, were measured, and the corresponding chronologies were developed. The relationships of these chronologies with the monthly mean temperature and monthly precipitation were explored via correlation analysis. Results show that the DBI chronology is closely related to the temperature in August of the current year, indicating that BI, specifically delta BI, data are suitable for use in dendroclimatology studies in subtropical areas. The resultant mean temperature reconstruction for August, based on DBI, explains 40.8% of the temperature variance and is robustly validated using independent periods from the calibration. This pilot study not only highlights the potential of DBI for temperature reconstruction in China but also offers valuable insights into historical climate variations in the Shennongjia region. Moreover, it shows the potential for utilizing such tree-ring data from low-latitude regions to derive past climate data in subtropical warm-humid zones. Peer reviewed